Stereological analysis of vascular network of subcortical auditory centers - Tatjana Bućma; Zdenka Krivokuća; Igor Sladojević (Biomedicinska istraživanja, 2022)
Introduction. Subcortical auditory centers have several sources of blood supply. Cochlear nuclei are vascularized by the anterior inferior cerebellar artery. Superior cerebellar and posterior cerebral arteries supply the inferior colliculus nucleus, while the medial geniculate body nucleus is supplied by several posterior cerebral artery branches. The aim of the research was to quantify the vascular network of subcortical auditory centers. Methods. Twelve adult brains, both sexes, aged 21 to 78 years, without signs of neurological diseases were analyzed in this study. Samples for histological sections, stained by the Mallory method, were obtained from strata cut at levels: the junction of the middle and rostral thirds of the oliva, the inferior colliculi, and the thalamic pulvinar. Volume, surface, and length density of the vascular network of subcortical auditory centers were analyzed stereological parameters. Results. All parameters had the highest values in the medial geniculate body nucleus. Statistically significant difference was found in the volume, surface, and length density between vascular networks of the cochlear nuclei and medial geniculate body nucleus, and between inferior colliculus nuclei and medial geniculate body. Vessels in cochlear nuclei and inferior colliculus nuclei differed only in length density. Conclusion. Cochlear nuclei and inferior colliculi nuclei blood vessels have a similar density and diameter, but vessels in inferior colliculi nuclei are more tortuous. In the medial geniculate body nucleus vessels are larger, denser and more tortuous compared to the other two subcortical auditory centers